Jenjang Karir Mempengaruhi Kinerja Pendokumentasian Asuhan Keperawatan pada Perawat Klinik - Abida Hanifa Wear; Samsualam; Andi Mappanganro; Tutik Agustini (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Professionalism is a requirement for the nursing profession in carrying out their duties in nursing services where nurses are an important resource for providing quality health services. One of the supports for nurse professionalism is through the development of a nursing career path. Nursing career path is a system that improves nurse performance and improves nurse skills. This research is a quantitative study using a cross-sectional design that aims to determine the effect of nurse level on nurse performance in documenting nursing care. Sampling used the total sampling method, namely a total of 82 nurses, with a research instrument of understanding and perception questionnaires about the career path of clinical nurses as well as clinical nurse performance questionnaires in documenting nursing care. The data analysis technique used was univariate and bivariate, where bivariate used the Chi-Square test. The results of the statistical analysis using the Chi-Square test obtained a value of ρ 0.004 or less than a (0.05) so it can be concluded that there is an effect of level clinical nurse career on the performance of clinical nurses in documenting nursing care at the Ibnu Sina Hospital UMI Makassar. Suggestions are that nurses are expected to be able to increase their responsibility towards their duties, including documenting nursing care and making sure to do the documentation carefully, accurately and on time